Bride of Ignat. Volume 1 - Mori, Moyori (Lovelove, Tokyopop, 2026)
"All I need from you... is to stay alive. "In a remote mountain village, the legend of the Snowy Mountain Dragon is sacred -- and so is the ritual that names Rita the dragon's bride. Chosen by tradition and bound by duty, Rita ascends the mountain to confront his fate... only to find himself stranded in a blizzard. Rita is rescued from the snow by Ignat -- a breathtaking dragon in human form. Yet the dragon of legend declares he no longer needs a bride. Determined not to be cast aside, Rita searches for meaning in his sacrifice... With Ignat's help, he begins to piece together the dragon's long-lost history, and discovers something far more dangerous than rejection: the ancient power that turns humans into dragons... "